Relationship Of Role Conflict And Mental Workload With Stress In Female Teachers At Junior High Schools In Banjarsari District, Surakarta - Della Nindhi Hariadhi; Sheena Ramadhia Asmara Dhani; Mitoriana Porusia (JURNAL KESMAS DAN GIZI (JKG), 2026)
The increasing involvement of women in the workforce often places them in two roles at once, namely as workers and housewives. This condition has the potential to cause role conflict and increase mental workload which ultimately triggers work stress. This study is to analyze the relationship between role conflict and mental workload with stress in female teachers at Junior High School in Banjarsari District, Surakarta. This study applied a quantitative approach and a cross-sectional approach from February to March 2025. A total of 160 female teachers were respondents obtained using a proportional random technique from a total population of 273 people. Data collection through the WFCS, NASA-TL, OSI-R questionnaires were analyzed using the Chi-square test. The findings of this study indicate that the majority of respondents are in the moderate category for role conflict, mental workload, and work stress. Statistical analysis revealed a relationship between dual role conflict and job stress (p = 0.000) and between mental workload and job stress (p = 0.001). These findings indicate that increasing levels of dual role conflict and mental workload are associated with increasing levels of job stress in female teachers. Therefore, dual role conflict and mental workload are important factors influencing job stress in female teachers, necessitating better workload management and support for work-family role balance to reduce stress and improve teacher well-being.